Institutional structures and financial market development in Africa - Otuo Serebour Agyemang; John Gartchie Gatsi; Abraham Ansong (Cogent Economics & Finance, 2018)
Our paper examines the relationship between institutional structures and the level of financial markets development in Africa. Our paper contributes to the extant literature by using other financial market development variables-ease of access to loans and venture capital availability-that have not before been used to analyzed how institutional structures influence the level of financial markets development in the context of Africa. We employ a two-step generalized method of moment estimator with corrected standard errors to examine this. We demonstrate that a high-quality institutional environment is relevant in explaining ease of access to loans and venture capital availability in Africa. Based on these results, our paper argues that good institutional structures could help stimulate the level of financial markets development in Africa. However, to attain this feat, African governments need to strengthen institutions through effective enforcement of laws to foster compliance in a specifically definite manner-by fashioning out costs for non-compliance
Keywords: 330; institutional structures; institutions; financial markets; financial market; development; African countries